MANAJEMEN NYERI PASIEN RAWAT JALAN PADA KASUS HERNIA NUKLEUS PULPOSUS MELALUI CORE STABILITY - Elsa Roselina; Safrin Arifin; Hermito Gidion (Program Pendidikan Vokasi Universitas Indonesia, 2014)
Abstract - Herniated nucleus pulposus (HNP) is a situation where the annulus fibrosus along nucleuspulposus protruding into the spinal canal. HNP patients often complain of back pain radiating to the lowerlimbs, especially when bending activity. Rehabilitation programs do to help reduce the pain. The aim of thisresearch knew which treatment was more effective among William's Flexion compared to Core Stability inreducing pain for HNP patients. This study used a double-blind experimental design with an alpha value of5%. The study was conducted at the Clinic “X”. Sample was 18 patients with medical diagnoses HNPundergoing therapy from September to December 2013, taken with randomization techniques. Pain wasmeasured using the Visual Analoque Scale (VAS). The results of the t-test analysis showed that Core stability(mean=4.56, SD=1.130) was more effective than William's flexion [mean = 2.78, SD = 0.972; t(16) = -3.578, p = 0.003] in reducing pain for HNP patients. The results of One-Way ANOVA showed that therewas no significant difference in pain reduction produced by William's flexion frequency of treatment [F(2,6)=1.857, p=0.236]. In contrast, there were significant differences in pain reduction produced by Corestability frequency treatment [F(1, 6)=12.333, p=0.007].Keywords: Core stability, Herniated Nucleus Pulposus